Plasmid incompatibility and control of replication: copy mutants of the R-factor R1 in Escherichia coli K-12. - Uhlin, B E (1975)
Plasmid incompatibility was studied in Escherichia coli K-12. By double-antibiotic selection, clones were constructed that carried the two R-factors R1 and R100, both belonging to the compatibility group FII. After release of the selection pressure, each of the two plasmids was lost at the same rate (8% per generation). Mutants of R-factor R1 showing an increased number of copies per chromosome (copy mutants) were tested for their incompatibility towards R-factor R100. The results indicate that plasmid incompatibility is quantitative and not just a qualitative property. All copy mutants studied affected incompatibility, and there were two classes of mutants: one increasing and one decreasing the incompatiblity exerted towards the test plasmid R100. Evidence is presented that incompatibility is related to the mechanisms that control replication. The implications of such a relation on proposed models for control of replication are discussed. The data do not support the hypothesis that plasmid incompatibility is due to competition for a replicational or segregational site.